KENDALI LAJU TETESAN INFUS DENGAN MENGGUNAKAN KONTROL PID - Liya Yuni Astutik; Diki Mardiantoro; Binti Khoirun Na’im; Sulfan Bagus Setyawan; Hanum Arrosida (IST AKPRIND Yogyakarta, 2018)
Now in health technology benefitable by intravenous therapy (IV) to used replace liquid and can balancing electrolyte in body. But in now using intravenous therapy (IV) uncontrol and unmonitoring can make people was flebitis (blood artery infection caused by chemical and drug irritation.In that condition then we proposed a intravenous therapy drop rate control based on PID. In that reseach will be expended in four work process. In first process is readability intravenous therapy drop who will do by photodiode sensors, in second process is to control automatic intravenous therapy drop rate used with PID controller who will do by Motor Servo when get instruction from smartphone, in third process is readability blockage Intravenous therapy liquid or doesn’t based on there are or no drip intravenous therapy and the fourth process is early warning system for Intravenous therapy liquid as one way to anticipation for Intravenous therapy liquid wear out on patient. Based on experiment shown that control automatic intravenous therapy drop rate had a good result. Getting it being showed of setting time value that can be reached is 16 second And error steady state value is 13 drips